Pengendalian Kualitas Proses Pembuatan Botol 600 ml Menggunakan Metode Statistical Process Control (SPC) dan Failure Mode and Effect Analysis (FMEA) - Rahmayanti, Dina; Wirdianto, Eri; Meuthia, Yumi; Kurnia Sandi, Devid (SURYA TEKNIKA, 2026)
Product quality is the main factor determining the competitiveness of bottled drinking water (AMDK) companies. PT Amanah Insanillahia, as one of the AMDK producers, still faces problems related to the high number of defective products, especially in the 600 ml bottle manufacturing process, with an average defect percentage of 1.40%, exceeding the company’s target of 1.00%. This study aims to identify the dominant types of defects and propose quality control improvement measures for the 600 ml bottle manufacturing process. The research data consist of primary and secondary data collected through observation, interviews, and production documentation. The methods used in this study are Statistical Process Control (SPC) supported by process mapping, Critical to Quality (CTQ), check sheets, Pareto diagrams, and fishbone diagrams, as well as the Failure Mode and Effect Analysis (FMEA) approach. The results show that the Body/Bottom wavy defect is the most dominant type of defect based on Pareto analysis. According to the FMEA analysis, the main causes of defects originate from machine factors, work methods, and human factors. The proposed priority improvements include the preparation of Standard Operating Procedures (SOPs), clear work instructions, and operator training to reduce defect rates and improve product quality.